Characteristics of moving ionospheric disturbances over Ukraine and West Antarctica during the strong geospace storm according to data of vertical sounding and incoherent scattering - V.V. Barabash; S.V. Panasenko; K.D. Aksonova; V.N. Lisachenko (Ukrainian Antarctic Journal, 2017)
The aim of the work is to obtain a new information about traveling ionospheric disturbances (TIDs) over Antarctica and Ukraine during the strong geospace storm of November 13 – 14, 2012 using the ionosonde of the Ukrainian Antarctic Akademik Vernadsky station and the incoherent scatter radar of the Institute of Ionosphere (Kharkiv). Methods. Radiophysical technique of remote radiosensing and method of system spectral analysis of the data were used to identify and evaluate the parameters of TIDs. Results. In order to detect the features of the morphology of TIDs in high and medium latitudes, the studies of thecharacteristics of TIDs over Antarctica and Ukraine were carried out before, during and after the strong geospace storm of November 13 – 14, 2012. It is shown that the amplitude of absolute variations of the electron density over Antarctica during the day of the storm (November 14) decreased in about two times compared with the reference day. It is determined that TIDs exist in both regions both in quiet conditions and during geospace disturbances. Ionospheric disturbances over a wide range of periods from 80 to 340 min have been observed over Antarctica. At the same time, over Ukraine, their values were generally equal to 60 minutes and 120 – 250 minutes. For reliable separation of wave processes caused by geocosmic storms and generated by other sources, it is necessary to continue joint systematic observations.